CONSUMER REVIEWS AND RECOMMENDATIONS AS FACTORS IN E-COMMERCE: LEGAL REGULATION CHALLENGES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article provides an overview of the current legal regulation practices concerning consumer reviews published online in developed countries and the Republic of Uzbekistan. Online reviews play a crucial role in e-commerce, serving as a valuable source of information for both consumers and businesses. The article examines the evolution of international standards for regulating online reviews and recommendations. It also discusses the three sets of guidelines on online reviews and recommendations issued by the International Consumer Protection and Enforcement Network, targeting business owners and marketers, review administrators, and influencers. The steady growth of e-commerce in Uzbekistan raises the question of the need for legal regulation in this area. The article analyzes the current state and future prospects for regulating online consumer reviews and recommendations in Uzbekistan.